2018
DOI: 10.1177/0022487118767645
|View full text |Cite
|
Sign up to set email alerts
|

Lessons for Teacher Education: The Role of Critical Professional Development in Teacher of Color Retention

Abstract: With disproportionately high attrition rates for teachers of Color, there are many lessons to be learned from veteran teacher leaders that can inform how we train teachers. In this article, I share analysis of interviews with 11 women of Color veteran teachers who serve in formal or informal leadership roles within social justice education. Their reflections reveal how teacher education programs—justice oriented or not—fell short in preparing them for the hostile racial climate of schools, thus putting them at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 36 publications
3
64
1
Order By: Relevance
“…In Kohli's (2019) research findings, he revealed that preparing professional teachers needed justice-oriented education so that it succeeded in developing a peaceful climate that was far from hostile in attitude. Racial literacy is also urgently needed as a frame to the development of critical professionalism that will help teachers in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In Kohli's (2019) research findings, he revealed that preparing professional teachers needed justice-oriented education so that it succeeded in developing a peaceful climate that was far from hostile in attitude. Racial literacy is also urgently needed as a frame to the development of critical professionalism that will help teachers in the field.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to practicing teachers, professional development is often cited as one possibility to help with retention (Brill & McCartney, 2008; Kohli, 2019; Mollenkopf, 2009). The specific challenges of the Latinx Spanish teachers in this study revealed a need for professional development that goes beyond best practices in language teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the efforts to recruit and retain prospective teachers of color, less empirical research has been reported on the preparation of prospective teachers of color to teach diverse students (Gist, 2017; Gist, Flores, & Claeys, 2014; Rogers-Ard, Knaus, Epstein, & Mayfield, 2013; Sleeter, Neal, & Kumashiro, 2014; Villegas & Davis, 2008). The curriculum, instructional strategies, and fieldwork in most teacher education programs that emphasize the preparation of middle-class, White teachers (Cochran-Smith et al, 2015) take little consideration of the diversity of prospective teachers (Gist, 2014; 2017; Kohli, 2019), nor have they focused much attention on the specific needs of prospective teachers of color in learning to teach diverse students in K–12 classrooms (Brown, 2014). Two examples come from Brown’s (2014) review of literature on preparing preservice teachers of color: Quiocho & Rios, 2000 found that preservice teachers of color often feel that their education programs are not preparing them to teach “effectively, both students from diverse backgrounds and across multiple school contexts,” while Téllez (1999) finds that teacher education programs fail to engage the knowledge prospective teachers of color possess as well as fail to prepare them to teach all students.…”
Section: Changes In Teacher Education Practicementioning
confidence: 99%
“…Irizarry (2007) and Kohli (2014) both documented how prospective teachers of color endured institutional racism such as overtly racist comments or actions and racial hierarchies. Similarly, Kohli (2019) studied 11 women teachers of color about their teacher preparation experiences, finding that they believed their teacher preparation programs not only marginalized them in their preparation but also continued to negatively affect their careers as they entered the field with limited tools to resist racialized structures. Gist (2017) explored the program and pedagogical experiences of teacher candidates of color, finding that prospective teachers experience a lack of culturally and linguistically responsive learning in their teacher education programs.…”
Section: Changes In Teacher Education Practicementioning
confidence: 99%